Neurotechnological applications and the protection of mental privacy: an assessment of risks - López-Silva, Pablo; Wajnerman-Paz, Abel; Molnár-Gábor, Fruzsina (Neuroethics, 2024)
The concept of mental privacy can be defined as the principle that subjects should have control over the access to their own neural data and to the information about the mental processes and states that can be obtained by analyzing it. Our aim is to contribute to the current debate on mental privacy by identifying the main positions, articulating key assumptions and addressing central arguments. First, we map the different positions found in current literature. We distinguish between those who dismiss concerns about mental privacy and those who endorse them. In this latter group, we establish a further disagreement between conservative and liberal strategies to protect mental privacy. Then, we address the first discussion by articulating and criticizing different skeptical views on mental privacy. Finally, we try to identify what are the unique features of neural data and examine how they may be connected to the ways in which neurotechnological mindreading could put mental privacy at risk. We suggest that even if neural data is unique, it may not require new strategies to protect people from its misuse. However, identifying the special features and risks of neurotechnological mind-reading is necessary for the second discussion on mental privacy to properly take off.